An Over Review to Origanum vulgare L. and its Pharmacological Properties - Mohammad Reza Morshedloo; Hasan Ahmadi; morteza pirali hamedani; Darab Yazdani (Institue of Medicinal Plants, ACECR, 2018)
Oregano (Origanum vulgare L.) is one of the most selled culinary and medicinal herb throughout the world. Flowering aerial parts and leaves of oregano have been used as a popular flavoring of food stuffs and as an antioxidant agent in cosmetics. Oregano contains a wide array of active components, including flavonoids, phenolic acids and glucosides, phenols and triterpenes. Several biological activities namely antibacterial, antifungal, antiviral, antidiabetic, antispasmodic, antimelanogenesis and antiproliferative have been demonstrated for oregano-based essential oils and extracts. Among the main bioactive constituents of these products, the phenols carvacrol and thymol, and the phenolic rosmarinic acid and origanoside proved to be strong antioxidant, anti-inflammatory and cardioprotective agents.